Przydatność rokownicza nowych markerów w przewlekłej skurczowej niewydolności serca = The prognostic usefulness of new markers in chronic systolic heart failure - Surowiec, Agnieszka; Rogowicz, Daniel; Wołowiec, Łukasz; Kochański, Bartosz; Wołowiec, Małgorzata; Plaskiewicz, Anna; Krakowska, Alicja; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Surowiec Agnieszka, Rogowicz Daniel, Wołowiec Łukasz, Kochański Bartosz, Wołowiec Małgorzata, Plaskiewicz Anna, Krakowska Alicja, Zukow Walery. Przydatność rokownicza nowych markerów w przewlekłej skurczowej niewydolności serca = The prognostic usefulness of new markers in chronic systolic heart failure. Journal of Education, Health and Sport. 2015;5(8):11-22. ISSN 2391-8306. DOI 10.5281/zenodo.22209 http://dx.doi.org/10.5281/zenodo.22209 https://pbn.nauka.gov.pl/works/599236 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-8513eaa7-5cb2-478b-9e97-a2125f241da8 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A11-22 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Przydatność rokownicza nowych markerów w przewlekłej skurczowej niewydolności serca The prognostic usefulness of new markers in chronic systolic heart failure Agnieszka Surowiec1, Daniel Rogowicz1, Łukasz Wołowiec1, Bartosz Kochański2, Małgorzata Wołowiec3, Anna Plaskiewicz2, Alicja Krakowska2, Walery Zukow4 1Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3Koło Naukowe Psychologii Zarządzania, Katedra Nauk Społecznych, Katolicki Uniwersytet Lubelski Jana Pawła II 4Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Przewlekła skurczowa niewydolność serca (PNS) jest chorobą o złożonej symptomatologii. PNS dzieli się na skurczową oraz na niewydolność serca (NS) z zachowaną frakcją wyrzutową. Choroba ta występuje u około 1-2% dorosłych w krajach rozwiniętych, natomiast u osób >70 roku życia odsetek ten stanowi >10%. Niewydolność serca stanowi jedną z wiodących przyczyn śmierci i niepełnosprawności na świecie, ponadto charakteryzuje się stale rosnącą zapadalnością. W przebiegu tej choroby w mięśniu sercowym dochodzi do niekorzystnych zmian, które mogą zostać zatrzymane lub nawet cofnięte poprzez wczesne, odpowiednie i zintensyfikowane leczenie. Chorzy na PNS stanowią niejednorodną grupę, a wpływ na stężenie peptydów natriuretycznych mają różne czynniki kliniczne, takie jak wiek, płeć, funkcja nerek, funkcja tarczycy, indeks masy ciała oraz niedokrwistości. Ponadto ocena stężenia peptydów natriuretycznych nie charakteryzuje wszystkich mechanizmów, które stanowią podłoże niewydolności serca. Zarówno chorzy ze skurczową PNS jak i chorzy z zachowaną frakcją wyrzutową mają podobne objawy, ale różne przyczyny patofizjologiczne NS oraz odmienną odpowiedź na leczenie. Na skutek tych wszystkich ograniczeń peptydów natriuretycznych w dalszym ciągu poszukuje się nowych markerów, które w lepszy i dokładniejszy sposób będą oceniały rokowanie chorych na PNS w praktyce klinicznej. Celem pracy jest przedstawienie roli wybranych nowych markerów w stratyfikacji ryzyka chorych z przewlekłą skurczową niewydolnością serca. Abstract Chronic systolic heart failure (CHF) is a disease with complex symptomatology. Chronic CHF can divided into systolic and heart failure (NS) with preserved ejection fraction. Approximately 1-2% of adults suffer from the disease in the developed countries, whereas it affects >10% of patients > 70 years of age. Heart failure is one of the leading causes of death and disability in the world, furthermore it is characterized by an ever-increasing incidence. In the course of the disease adverse changes take place in the heart muscle, however, these changes can be stopped or even reversed by timely, relevant and intensified treatment. Patients with CHF are a heterogeneous group and the influence on the concentration of natriuretic peptides have various clinical factors such as age, sex, renal function, thyroid function, body mass index and anemia. Moreover, the evaluation of natriuretic peptides does not characterize all the mechanisms that underlie heart failure. Both patients with systolic CHF and patients with preserved ejection fraction have similar symptoms but different pathophysiological causes of NS and a different response to treatment. As a result of all these limitations related to natriuretic peptides there are still searches for new markers that will assess the prognosis of CHF patients in clinical practice better and more accurately. The aim of the study is to present the role of new (selected) markers in risk stratification of patients with chronic systolic heart failure. Słowa kluczowe: przydatność rokownicza, markery, przewlekła skurczowa niewydolność serca. Key words: prognostic usefulness, markers, chronic systolic heart failure.